2013
DOI: 10.1021/jf401536y
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Thermal Stability Enhancement of Leaf Essential Oils and Their Main Constituents from Indigenous Cinnamon (Cinnamomum osmophloeum)

Abstract: The thermal stability of leaf essential oils from various Cinnamomum osmophloeum and their constituents was investigated for the first time. The results indicated that trans-cinnamaldehyde (Cin) content in eugenol-free essential oil from C. osmophloeum was affected by high temperatures. The retention of Cin (RC) decreased to 17.4% after the essential oil was incubated for 8 h at 100 °C. In contrast, essential oils containing eugenol showed greater thermal stability. Seven kinds of antioxidants were added to Ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 28 publications
1
38
0
4
Order By: Relevance
“…Terpinenes: Borneol; camphene; camphor; limonene; linalool; myrcene; p-cymene; spathulenol; viridiflorol; b-caryophyllene; b-pinene; d-cadinene; ⍺-cadinol; ⍺pinene; ⍺-terpineol [176] [209] Kaempferol glycosides: [210] Anticancer, [130,211] antidiabetic, [212,213] antidyslipidaemic, [214] antiinflammatory, [209,215] antimicrobial [216,217] , antioxidant, [213,218] cardioprotective, [219] cytotoxicity, [220] hair growth, [221] hepatoprotective, [222] hypolipidaemic effect, [223] hypouricaemic effects, [224] immunomodulatory, [225] larvicidal, [29] pancreas-protective effect, [226] tyrosinase, [220,227] wound healing, [227] xanthine oxidase inhibitory [224] Arthritis, [228] cough and cold, [228] diabetes, [228] infection, [222] inflammation, [228] nerve pains, [228] pyrexia [228] Bark Flavonoids: (E)-Cinnamaldehyde; (Z)cinnamaldehyde. [229] Hydrocarbon: Phenol; c-muurolene [229] Flavonoids: cis-Cinnamaldehyde; transcinnamaldehyde [5,230,231] ; cinnamaldehyde. [232] Hydrocarbon: c-Cadinene; d-cadinene; ⍺-copaene [232] ; copaene.…”
Section: Leavesmentioning
confidence: 99%
See 1 more Smart Citation
“…Terpinenes: Borneol; camphene; camphor; limonene; linalool; myrcene; p-cymene; spathulenol; viridiflorol; b-caryophyllene; b-pinene; d-cadinene; ⍺-cadinol; ⍺pinene; ⍺-terpineol [176] [209] Kaempferol glycosides: [210] Anticancer, [130,211] antidiabetic, [212,213] antidyslipidaemic, [214] antiinflammatory, [209,215] antimicrobial [216,217] , antioxidant, [213,218] cardioprotective, [219] cytotoxicity, [220] hair growth, [221] hepatoprotective, [222] hypolipidaemic effect, [223] hypouricaemic effects, [224] immunomodulatory, [225] larvicidal, [29] pancreas-protective effect, [226] tyrosinase, [220,227] wound healing, [227] xanthine oxidase inhibitory [224] Arthritis, [228] cough and cold, [228] diabetes, [228] infection, [222] inflammation, [228] nerve pains, [228] pyrexia [228] Bark Flavonoids: (E)-Cinnamaldehyde; (Z)cinnamaldehyde. [229] Hydrocarbon: Phenol; c-muurolene [229] Flavonoids: cis-Cinnamaldehyde; transcinnamaldehyde [5,230,231] ; cinnamaldehyde. [232] Hydrocarbon: c-Cadinene; d-cadinene; ⍺-copaene [232] ; copaene.…”
Section: Leavesmentioning
confidence: 99%
“…[2] Around 250 species of this genus are identified around the world. [3,4] Different parts contain some primary constituents, that is cinnamaldehyde and trans-cinnamaldehyde (Cin), present in the essential oil of its bark contributing to the fragrance and various biological activity, [5] eugenol (leaf) inhibit several different MDR pathogenic bacteria [6,7] and camphor (root). [8] This genus contains four main economically important cinnamon species, that is Cinnamomum verum ('true cinnamon', Sri Lankan or Ceylon cinnamon), Cinnamomum cassia (Chinese cinnamon), Cinnamomum burmannii (Java or Indonesian cinnamon) and Cinnamomum loureiroi (Vietnamese or Saigon cinnamon).…”
Section: Introductionmentioning
confidence: 99%
“…The most important constituents of cinnamon are cinnamaldehyde and trans -cinnamaldehyde (Cin), which are present in the essential oil, thus contributing to the fragrance and to the various biological activities observed with cinnamon [4]. A study on Cinnamomum osmophloeum ( C .…”
Section: Introductionmentioning
confidence: 99%
“…They also own antioxidant activities (11). In the same way, the most important ingredients of cinnamon is trans-cinnamaldehyde or cinnamaldehyde (Figure 1), which exists in the essential oil, therefore donating to the fragrance and to the diverse biological activities perceived with cinnamon (12). Equally important, in 2008, a study by Chang et al on Cinnamomum osmophloeum demonstrated that the essential oil from cinnamon leaves includes a high level of cinnamon.…”
Section: The Therapeutic Effect Of Cinnamon On Hypertensionmentioning
confidence: 99%